Local Wisdom: Deskripsi, Tantangan, dan Peluangnya dalam Penelitian Interpretif - Supatmi Supatmi (Perspektif Akuntansi, 2019)
This paper aims to describe the use of local wisdom concepts in accounting and business research and finds the challenges and opportunities of using local wisdom concepts for intepretive researchers in Indonesia for international publication purposes. By using 60 articles published in national and international journals, the description results that local wisdom is widely used in the management accounting studies, with the type/form of local or tribal culture, and many use ethnography as a research method. Learning from 12 articles published in reputable international journals, challenges and opportunities for the use of local wisdom concepts in order to deserve publication in international journals, we have to concern about research methods, types/forms of local wisdom, and improve mental courage.